Optimalisasi Digital Marketing dalam Promosi dan Jaringan di SMKS Wikrama 1 Garut - - Ernawati; Budi Harto; Verra Rosyalia Widia Sofyan; Untung Eko Setyasari; Yanti Fadila Wahab (Politeknik Negeri Cilacap, 2026)
The advancement of digital technology compels educational institutions to optimize digital media-based promotional strategies to enhance the visibility and competitiveness of schools. In a specific context, SMKS Wikrama 1 Garut faces challenges in the form of limited human resources, variations in digital literacy, and the absence of a consistent and structured digital marketing strategy. Although many studies emphasize the role of digital marketing in educational institutions, there is still a knowledge gap that includes a lack of integration of technology adoption theory, utilization of internal resources, and long-term relationship strategies in the context of vocational schools in rural areas. This research employs a qualitative-descriptive approach through in-depth interviews, field observations, and document analysis to explore the current conditions and strategies for optimizing digital marketing in schools. The results of the study show that the use of platforms such as Instagram, TikTok, Facebook, and YouTube is still sporadic, lacks data-driven approaches, and does not optimally showcase the school's vocational identity and narrative; content management is influenced by low perceptions of ease of use, limited strategic resources, and the absence of an editorial calendar; while the use of short videos and storytelling has been proven to generate the highest engagement but has not been implemented consistently. The analysis also identified that school websites have not been optimized through SEO, and collaboration with alumni and industry has not been maximized as strategic content. This research implicitly emphasizes the necessity of a theory-based digital marketing strategy, utilizing data and internal resources to enhance promotion while simultaneously establishing sustainable institutional networks.